2016
DOI: 10.1111/gbi.12222
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the spatial heterogeneity of Ediacaran carbon cycling

Abstract: 23 Records of the Ediacaran carbon cycle (635 to 541 million years ago) include the 24Shuram excursion (SE), the largest negative carbonate-carbon isotope excursion in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 69 publications
(177 reference statements)
6
58
1
1
Order By: Relevance
“…DY, Dengying Formation; NS, Nikol'skaya Formation; NT, Nantuo Formation; UF, Urinskaya Formation. δ 13 C carb profile of the Jiulongwan section is from Li et al (). δ 13 C carb profile of the Bol'shoy Patom section is from Melezhik et al ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DY, Dengying Formation; NS, Nikol'skaya Formation; NT, Nantuo Formation; UF, Urinskaya Formation. δ 13 C carb profile of the Jiulongwan section is from Li et al (). δ 13 C carb profile of the Bol'shoy Patom section is from Melezhik et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The SE at the Jiulongwan section (GPS: N 30°48'15.05″, W 111°3'18.61″) is represented by the Doushantuo Member III (Li et al, ; McFadden et al, ), which is about 70 m thick. The lower 40 m is composed of dolostone with bedded chert, and the upper 30 consists primarily of ribbon limestone (see figure 4 in the Supplementary Information of McFadden et al, for a detailed summary of the stratigraphy at the Jiulongwan section).…”
Section: Study Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies have suggested that the Shuram NCIE may be related to a period of ocean oxygenation (e.g., Fike et al, ; McFadden et al, ), resulting in the oxidation of a massive 13 C‐depleted dissolved organic carbon (DOC) reservoir in the deep ocean (Fike et al, ; Jiang et al, ; McFadden et al, ; Rothman, Hayes, & Summons, ). However, recent studies also suggested that local heterogeneous and transient oxygenation may have played a critical role in the expanded spatial heterogeneity of δ 13 C and δ 34 S excursions, not only from the Doushantuo Formation shales but also from carbonate platform regions worldwide during the Ediacaran (Li et al, ; Loyd et al, ; Osburn, Owens, Bergmann, Lyons, & Grotzinger, ; Shi et al, ). Therefore, the challenge is to establish the global extent of oceanic redox conditions for this period, which is important for understanding the connection between oceanic oxygenation and the radiation of Ediacaran‐type biota because the oldest Avalon Assemblage occurs in a deep‐water, volcaniclastic setting of the Avalon Zone of Newfoundland (Narbonne, ).…”
Section: Introductionmentioning
confidence: 99%
“…3). This discordance may be attributed to more intense diagenetic alteration of the dolostones of the upper Platonovskaya Formation in the stratotype, or to local synsedimentary variations in carbon-isotope fractionation in remote zones of a basin (Klaebe et al 2016;Li et al 2016;Schmid 2017).…”
Section: Litho-and Chemostratigraphical Correlations Of the Platonovsmentioning
confidence: 99%